Mitochondrial methylation is linked to sexually dimorphic growth in Nile tilapia (Oreochromis niloticus) - Tripathy, Partha Sarathi; Siriyappagouder, Prabhugouda; Nedoluzhko, Artem Valeryevich; Konstantinidis, Ioannis; Dash, Soumya Shephalika; Behera, Bijay Kumar; Parhi, Janmejay; Skjærven, Kaja; Piferrer, Francesc; Fernandes, Jorge Manuel de Oliveira (Frontiers in Cell and Developmental Biology, 2025)
For aquaculture to be sustainable, it is very important to improve the growth rates of farmed fish by choosing the right species and their management. However, the integration of epigenetic markers in selective breeding programs remains underdeveloped, mainly due to limited understanding, particularly regarding DNA methylation’s heritability and its functional impact on growth traits. This gap is even more pronounced in mitochondrial epigenetics, despite mitochondria’s critical role in energy production and growth regulation, making it an important but underexplored area in aquaculture breeding strategies. The present study aimed to explore the relationship between differential mitogenome methylation and its role in growth rates and sexual dimorphism in Nile tilapia (Oreochromis niloticus). Nanopore sequencing was employed to compare mtDNA methylation patterns between fast- and slow-growing individuals, as well as between sexes. We found significant differences in mtDNA methylation, with males exhibiting higher growth rates and distinct methylation patterns in genes related to the electron transport chain, such as ND5, ATP6 and CYTB. This suggests a link between mitochondrial function and growth. Moreover, several differentially methylated sites were identified, including hypomethylation in genes associated with oxidative phosphorylation, which correlated with increased growth. Notably, larger individuals showed significant hypomethylation in ND5, ND6 and COX1, potentially enhancing ATP production. The differentially methylated positions across mitogenome may drive enhanced growth by optimizing mitochondrial function for higher energy output. Our study provides valuable insights for selective breeding programs to enhance growth traits, emphasizing the need for future research on the functional role of these epigenetic changes in sustainable aquaculture.